1996
DOI: 10.1055/s-2007-994352
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Immunoreactive Endothelin-1 Concentrations in Infants with Persistent Pulmonary Hypertension of the Newborn

Abstract: Plasma concentrations of endothelin-1 (ET-1) have been reported to be elevated in children and adults with pulmonary hypertension. We hypothesized that infants with persistent pulmonary hypertension of the newborn (PPHN) have elevated plasma concentrations of ET-1. Plasma concentrations of immunoreactive-endothelin-1 (ir-ET-1) were measured using a radioimmunoassay in 20 infants with PPHN and 20 normal term infants. Mean birthweight and gestational age of the infants were comparable in the two groups. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…Intrauterine hypoxemia, infection, hyperglycemia, and drug exposure can result in an incomplete response to perinatal vasodilator stimuli and persistently elevated pulmonary arterial blood pressure, limited pulmonary blood flow, and severe central hypoxemia. Persistent pulmonary hypertension of the newborn (PPHN) is characterized by extrapulmonary shunting of blood across the patent foreman ovale and through the patent ductus arteriosus (DA), severe hypoxemia, high levels of circulating endothelin-1, decreased nitric oxide production, and vascular remodeling due to increased cell proliferation (1,3,13,14,29).Previous work from our laboratory demonstrated that pulmonary artery smooth muscle cells (PA SMC) derived from late-gestation fetal lambs directly sense an acute increase in oxygen tension and respond with activation of a calciumsensitive K ϩ (K Ca ) channel, membrane hyperpolarization, and a decrease in intracellular Ca 2ϩ ([Ca 2ϩ ] i ) (23). In contrast, in PA SMC derived from an ovine model of PPHN, K Ca channel expression is diminished, and an acute increase in oxygen tension has no effect on [Ca 2ϩ ] i (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine hypoxemia, infection, hyperglycemia, and drug exposure can result in an incomplete response to perinatal vasodilator stimuli and persistently elevated pulmonary arterial blood pressure, limited pulmonary blood flow, and severe central hypoxemia. Persistent pulmonary hypertension of the newborn (PPHN) is characterized by extrapulmonary shunting of blood across the patent foreman ovale and through the patent ductus arteriosus (DA), severe hypoxemia, high levels of circulating endothelin-1, decreased nitric oxide production, and vascular remodeling due to increased cell proliferation (1,3,13,14,29).Previous work from our laboratory demonstrated that pulmonary artery smooth muscle cells (PA SMC) derived from late-gestation fetal lambs directly sense an acute increase in oxygen tension and respond with activation of a calciumsensitive K ϩ (K Ca ) channel, membrane hyperpolarization, and a decrease in intracellular Ca 2ϩ ([Ca 2ϩ ] i ) (23). In contrast, in PA SMC derived from an ovine model of PPHN, K Ca channel expression is diminished, and an acute increase in oxygen tension has no effect on [Ca 2ϩ ] i (18).…”
mentioning
confidence: 99%
“…Intrauterine hypoxemia, infection, hyperglycemia, and drug exposure can result in an incomplete response to perinatal vasodilator stimuli and persistently elevated pulmonary arterial blood pressure, limited pulmonary blood flow, and severe central hypoxemia. Persistent pulmonary hypertension of the newborn (PPHN) is characterized by extrapulmonary shunting of blood across the patent foreman ovale and through the patent ductus arteriosus (DA), severe hypoxemia, high levels of circulating endothelin-1, decreased nitric oxide production, and vascular remodeling due to increased cell proliferation (1,3,13,14,29).…”
mentioning
confidence: 99%
“…Animal studies also suggested the role of impaired VEGF signalling in PPHN [9]. Elevated ET-1 levels are seen in PPHN concomitant with decreased eNOS activity and cGMP levels [18].…”
Section: Pathophysiologic Changes In Pphnmentioning
confidence: 99%
“…Elevated ET-1 levels have been demonstrated in animal models of meconium aspiration (7), in neonates with PPHN (3,8,9), and in older children (10) and adults (11) with pulmonary hypertension. Furthermore, the plasma ET-1 level appears to positively correlate with disease severity (8,9,12).Therapy for pulmonary hypertension in the neonate is currently targeted at preventing or reversing the sequelae of pulmonary endothelial dysfunction. iNO improves oxygenation and reduces the need for extracorporeal life support in some of the most severe cases (13).…”
mentioning
confidence: 99%
“…Elevated ET-1 levels have been demonstrated in animal models of meconium aspiration (7), in neonates with PPHN (3,8,9), and in older children (10) and adults (11) with pulmonary hypertension. Furthermore, the plasma ET-1 level appears to positively correlate with disease severity (8,9,12).…”
mentioning
confidence: 99%